The Challenge of Pancasila Values in the History Learning Process for Class XI IPS 2 in Even Semester at SMAN 10 Bandar Lampung - Rudi Irawan (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2023)
This study aims to find out the understanding and implementation of Pancasila values in students' lives and to improve history learning achievement amidst the fading of national identity due to global digitalization during the Covid-19 pandemic. Strengthening the learning of history determines how the implementation will have an impact on the quality of identity of the nation's children, by improving the quality of learning history, then automatically the inculcation and implementation of Pancasila values will have an impact on the lives of students. This study uses a classroom action research method through three cycles and a qualitative data approach, in which the learning process consists of an introduction, core activities, and closing accompanied by reflection on learning. The results showed that learning history using the cooperative learning method with the picture and picture model can improve the material understanding of Pancasila values for class XI IPS 2 students at SMAN 10 Bandar Lampung which is implemented in knowledge and behavior, both individually and in groups. Furthermore, the results of this study are expected to be able to increase material understanding of Pancasila values which are implemented in continuous activities at SMAN 10 Bandar Lampung.